2015
DOI: 10.1071/sh14168
|View full text |Cite
|
Sign up to set email alerts
|

Management of syphilis in HIV-positive individuals

Abstract: Since the turn of the millennium a sustained outbreak of syphilis among men who have sex with men continues, approximately 20-50% of whom have concurrent HIV infection. In this paper we aim to explore the controversies that exist around the management of syphilis in HIV-positive individuals. Not only do HIV-positive people have different clinical manifestations of syphilis they have higher rates of asymptomatic neurological involvement, slower serological response to treatment and higher serological failure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, a survey indicated that physicians in the United States and Europe opted for a more intensive regimen of antibiotics for HIV co-infected individuals. Major concerns lie in the dierence in clinical features in HIV, impaired host immunity, a higher rate of asymptomatic neurological involvement, and slower serological response (4). There was no notable serological difference in treatment of single-dose versus three-dose BPG in HIV co-infected individuals, suggesting that the international recommendation of a single dose of BPG is sucient in acute infection Benzathine penicillin G for malignant syphilis in HIV (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a survey indicated that physicians in the United States and Europe opted for a more intensive regimen of antibiotics for HIV co-infected individuals. Major concerns lie in the dierence in clinical features in HIV, impaired host immunity, a higher rate of asymptomatic neurological involvement, and slower serological response (4). There was no notable serological difference in treatment of single-dose versus three-dose BPG in HIV co-infected individuals, suggesting that the international recommendation of a single dose of BPG is sucient in acute infection Benzathine penicillin G for malignant syphilis in HIV (10).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no specic recommended treatment for MS (3). Although the most commonly used treatment regimen is three consecutive weekly intramuscular injections of 2,400,000-unit benzathine penicillin G (BPG), a single dose of BPG, which follows the recommendation of secondary syphilis treatment, may be adequate to treat MS (3,4). JHR is a transient reaction following antibiotic treatment, which may result from a high serology titer in MS (3).…”
Section: Introductionmentioning
confidence: 99%
“…Tipple summarises published reports on how syphilis may present differently in HIV-positive patients, while Cresswell and Fisher tackle the controversial question as to whether syphilis ought to be treated differently in patients with HIV. 17,18 Ho and Spudich delve into the complex area of neurosyphilis and critically review its diagnosis and management in the context of HIV, including the thorny issue of when lumbar punctures are indicated. 19 Turning to the biology of T. pallidum, Ma et al detail the typing methods that have been used to characterise different strains and make a case for the development of more discriminatory genotyping methods.…”
mentioning
confidence: 99%